The effect of a restriction policy on the antimicrobial consumption in Turkey: a country-wide study - Hosoglu, S; Esen, S; Ozturk, R; Altindis, M; Ertek, M; Kaygusuz, S; Celen, MK (Springer, 2005)
Background: The total annual expenditure of antimicrobials in Turkey in 2002 was 24% of all drug spending. In order to reduce the cost of drug expenditure, the Turkish government introduced a new restriction policy on the prescription of antimicrobials in June 2003. This new policy is based on the justification that the physicians specializing in infectious diseases should be primarily responsible for the prescription of antimicrobials. Objectives: Compare and contrast the usage of antimicrobials at hospitals before and after the implementation of the new restriction policy. Methods: The data was collected from the same departments in two different periods in 2003 at 15 hospitals throughout Turkey. The first set of data was collected a few days before the new policy was implemented in May 2003 and the second data set 6 months after that. Antimicrobial usage was calculated as defined daily doses (DDDs) per 100 patient days according to ATC-DDD index. The change in antimicrobial consumption was determined by comparing the mean DDD values before and after the implementation of the new policy. Results: Before the intervention, the mean antimicrobial use density was 71.56 DDD/100 patients-day at the hospitals in the study. Six months after the implementation, the mean antimicrobial use density was 52.64 DDD/100 patients-day. There was a 26.4% decrease in the antimicrobial usage between that prior to and that after the intervention (P < 0.025). Conclusions: The study shows that the implementation of the new policy resulted in a significant reduction in the prescription of antimicrobials.
Keywords: antimicrobial utilization; prescription restriction policy; IDP consultation